Telugu Christians : a history - Taneti, James Elisha, 1972- (Minneapolis : Fortress Press, 2022)
"Telugu Christianity is a local expression of a global religion. In this exciting book, James Elisha Taneti offers an introduction to the history of the Telugu Christian faith community, located primarily in the states of Telangana and Andhra Pradesh in south India. The volume analyzes how social aspirations of the community, local worldviews, and historical contingencies shape the beliefs and practices of Telugu Christians. By confessing the lordship of Christ, appropriating Christian practices, and affiliating with the global church, Telugu Christianity is equally Christian and Telugu"--page 4 of cover.
Acknowledgments -- Abbreviations -- Part I. Introduction -- Scattered beginnings -- A confluence of three worlds -- Women's leadership in the making of Telugu Christianity -- Part II. The Spirit at the edges: Telugu Pentecostals -- Consolidated centers and expansive edges -- The movements around and outside the church -- Conclusion -- Selected bibliography -- Index.
Includes bibliographical references (unnumbered page 185-page 198) and index.
Keywords: Christianity -- India -- Telangana; Christianity -- India -- Andhra Pradesh; Telugu (Indic people) -- India -- Religion